Pile driveability in low-to-medium density chalk - Buckley, R; Kontoe, S; Jardine, R; Barbosa, P; Schroeder, F (NRC Research Press, 2020)
Pile driving in low to medium density chalk is subject to significant uncertainty. Predictions of Chalk Resistance to Driving (CRD) often vary considerably from field driving behaviour, with both pile refusals and free falls under zero load being reported. However, recent field studies have led to better understanding of the processes which control the wide range of behaviour seen in the field. This paper describes the primary outcomes of the analysis of dynamic tests at an onshore and an offshore site and uses the results to propose a new method to predict CRD. The method is based on phenomena identified experimentally: the relationship between cone penetration resistance and CRD, the attenuation of local stresses as driving advances and the operational effective stress interface shear failure characteristics. The proposed method is evaluated through back analyses of driving records from independent pile installation cases that were not included in developing the method, but involved known ground conditions, hammer characteristics and applied energies. The proposed method is shown to lead to more reliable predictions of CRD than the approaches currently applied by industry.